Characterization of the Cultivable Microbiota in Fresh and Stored Mature Human Breast Milk - Schwab, Clarissa; Voney, Evelyn; Ramirez Garcia, Alejandro; Vischer, Michaela; Lacroix, Christophe (Frontiers in Microbiology, 2019)
Besides nutritional components, breast milk contains diverse microbes, which may be involved in colonization of the infant gut. Expressed milk is often stored for few days in the refrigerator. The aim of this study was to determine the abundance, prevalence and diversity of facultative and strict anaerobic bacteria using culture-dependent and -independent methods, and to determine changes in milk microbial and chemical composition during storage. Samples of mature breast milk from 21 women were collected 3-6 months post-partum and were analysed fresh or after anaerobic storage for 6 days at 4 °C. The cultivable bacterial population was analysed using the most probable number (MPN) method or plate counts and different media. The abundance of major bacterial groups was determined using quantitative PCR and 16S rRNA gene sequencing. Lactose, lactate, short chain fatty acids and human milk oligosaccharides (HMO) were analyzed using chromatography techniques. Highest mean viable cell counts were obtained in yeast casitone fatty acids (YCFA) broth supplied with mucin (log 4.2±1.8 cells/ml) and lactose (log 3.9±1.4 cells/ml), or Columbia agar (log 3.0±0.7 cells/ml). Mean total bacterial counts estimated by qPCR was 5.3±0.6 log cells/ml, with Firmicutes being the most abundant phylum. The most prevalent bacterial groups were Streptococcus spp. (15/19 samples), Enterobacteriaceae (13/19) and Lactobacillus/Lactococcus/Pediococcus groups (12/19). While the average total number of bacterial cells did not change significantly during storage, the prevalence of strict anerobic Bacteroidetes increased threefold, from 3/19 to 9/19, while in 7 samples Clostridum clusters IV or XIVa became detectable after storage. Major HMO were not degraded. Lactate was present in 18/21 samples after storage (2.3-18.0 mM). Butyrate was detected in 15/21 and 18/21 samples before and after storage, respectively, at concentrations ranging from 2.5-5.7 mM. We demonstrate enhanced prevalence and/or abundance of viable strict anaerobes from the Bacteroidetes and Clostridiales after 6-day anaerobic storage of human milk. Our data indicate that anaerobic cold storage did not markedly change total viable bacterial load, while HMO profiles were stable. Anaerobic cold storage of human milk for a up to 6 days may be suitable for preserving milk quality for potential microbial transfer to the infant gut.